Modeling Initiation and Detonation of Complex Explosive Formulations - Partom, Yehuda (European Journal of Applied Sciences, 2021)
Since 1980 we’ve developed and used our reactive flow model TDRR (= reactant Temperature Dependent Reaction Rate). TDRR makes it possible to calculate initiation and detonation of a single component explosive. It includes EOSs (Equations of State) for the reactant and products, and a reaction rate equation for the transition from reactant to products. As the EOSs and the reaction rate are calibrated for a certain formulation, say HV5 (95% HMX+5% Viton), it’s not possible to use them for a different formulation of the same materials, say HV15. Here we expand TDRR to handle general formulations with any number of components (explosives, binders and products). We call our expanded model TDRRF (F for Formulation). We first write down the model equations and then use them with two computed examples: 1) HVx and BFx formulations (x=explosive mass ratio, H=HMX, V=Viton, B=TATB, F=kelF) and 2) BHx formulations (x=B mass ratio).